The Effect of the HIV/AIDS Epidemic on Africa's Truck Drivers - Christopher M. Kribs-Zaleta; Melanie Lee; Christine Román; Shari Wiley; Carlos M. Hernández-Suárez (Mathematical Biosciences and Engineering)
The AIDS epidemic is having a growing impact on the transport sectorof the economy of sub-Saharan Africa, where long-distance truck driversare at an increased risk of infection due to their frequent contacts withcommercial sex workers. The spread of AIDS in the transport industry isespecially significant to the economy, as truck drivers are largely responsiblefor transporting crops and supplies needed for daily subsistence. In thispaper we analyze these effects via two models, one employing a switch andthe other a Verhulst saturation function, to describe the rate at which newdrivers are recruited in terms of the supply and demand for them in thegeneral population. Results provide an estimate of the epidemic's economicimpact on the transportation sector through the loss of truck drivers(an estimated 10% per year, with endemic levels near 90%).